“A subject dead is not worth presenting”: Cromwell, the Past, and the Haunting of Thomas Carlyle - McAllister, David (Romanticism and Victorianism on the Net, 2011)
This essay examines Thomas Carlyle’s painful struggle to write a book on Oliver Cromwell and the Puritan era in the years 1838 to 1845, and seeks to discover why this otherwise prolific author found it so difficult to produce a history of the man who occupied the central place in his pantheon of heroes. It does so by examining his metaphoric conception of the past as a body that could, if treated correctly by the historian, be presented “alive” rather than “dead,” and his feeling that the past and the voices of its “dead heroes” were haunting him like ghosts. The metaphoric construction and progress of this haunting is explored using critical approaches derived from Jacques Derrida and Paul de Man. By placing Carlyle’s crisis of authorship in conversation with these thinkers, I attempt to cast a new light on his relationship to the past and his sense of the difficulties involved in giving voice to the dead. It was only through a subjugation of his own authorial voice to that of his dead subject that Carlyle was able to bring an end to the haunting that had threatened to silence him in the early 1840s.